Wawasan Al-Qur’an Tentang Ulul Albab - Darnanengsih Darnanengsih; Hasyim Haddade; Hamka Hamka; Syahrul Syahrul (Al-Riwayah : Jurnal Kependidikan, 2026)
This study aims to explore the concept of Ulul Albab in the Qur'an through a thematic interpretation approach (tafsir maudhui) and library research method. The term Ulul Albab represents an ideal human figure in the Qur'anic perspective, characterized by the integration of intellectual clarity, spiritual consciousness, and moral integrity. The study collects and analyzes verses containing the term Ulul Albab, examining them through linguistic, historical, and exegetical perspectives from both classical and contemporary scholars. The findings indicate that Ulul Albab are individuals who actively use their intellect to reflect upon the signs of God, engage in constant remembrance of Him, and apply their knowledge into wise and meaningful actions. This concept remains highly relevant in addressing modern challenges of value disintegration and knowledge fragmentation, offering a holistic model for Islamic education and leadership development.